Family and developmental history of female versus male adolescents with ADHD: diagnosis-specific overlap, few gender/sex differences - Waltereit, Johanna; Zimmer, Jonas; Roessner, Veit; Waltereit, Robert (Frontiers in Psychiatry, 2023)
Background: Gender and sex differences in the development of children and adolescents are commonly found in the psychiatric examination. Family and developmental history is an important part of the clinical diagnostic interview, the basic examination technique. Attention-deficit/hyperactivity disorder (ADHD) is associated with diagnosis-specific markers in family and development history. However, it is unclear to what extent ADHD-specific signs and narratives differ between females and males. The aim of this study was to assess and to compare the family and developmental history profiles of female versus male adolescents with ADHD. Methods: Data were collected using the clinical diagnostic interview technique from parents of female and male patients diagnosed with ADHD (ICD-10 F90.0, F90.1 and F98.8) between the ages of 12 and 17 years (n = 92). The two groups were matched in pairs for sex, IQ and ICD-10 diagnosis (F90.0, F90.1 and F98.8). Interview data were operationalized in three categories: 0 - physiological marker, 1 - subclinical marker, 2 - clinical marker. The two groups were compared with two-way ANOVA. Results: Information about female in comparison to male adolescents were reported in the parental interview with few differences. Conclusions: Our study suggests that family and developmental history of the neurodevelopmental disorder ADHD is only poorly influenced by gender or sex.